CHRISTIAN FAITH AND THE EARTH: RESPICE ET PROSPICE EDITORIAL - Conradie, Ernst M. (Scriptura, 2012)
A number of contributions included in this volume of Scriptura are derived from parallel sessions at the culminating conference of the Christian Faith and the Earth project held at the Sustainability Institute near Lynedoch from 6 to 10 August 2012. This project was established in January 2007 to explore the content and ambiguous significance of the Christian faith for a time of ecological destruction. The aim has two components, namely to describe and assess the current state of the debate in Christian eco-theology and to offer a sense of direction for the way forward. The Latin phrase ‘Respice et Prospice’ that has been added as the conference title is also the motto of the University of the Western Cape that hosted the conference. doi: 10.7833/111-1-11